Editorial - Ali Kemal Ozdemir (Cumhuriyet Dental Journal, 2011)
Dear Colleagues, We are pleased that the September 2011 issue of the Cumhuriyet Dental Journal has published. Thank you very much to all authors and reviewers for their contributions. Dr. Rosenstiel, Dr. Mericske, Dr. Palma-Dibb, Dr. Ozcan, Dr. Cho, Dr. Sauro, Dr. Abdalla, Dr. Ozer, Dr. Nuvvula, Dr. Jafarzadeh, Dr. Tezvergil-Mutluay, Dr. Mutluay, and Dr. Gursoy have joined our editorial board. We are are grateful to them for joining our family. Our journal is now indexed in Index Copernicus and under evaluation in Ulakbim (Türk Tıp Dizini). We know that this is only the beginning and we hope that our journal will be indexed in expanded science citation index in the coming months. I owe a 'Thank you' to each and every member of our editorial board for their hard work. Hope to meet in the next issue. Prof. Dr. Ali Kemal Ozdemir Editor-in-Chief Cumhuriyet Dental Journal